Neuroinflammation in the Pathogenesis of Psychiatric Disorder - Sutantio, Eric Herlambang; Octaviani, Ines Damayanti (Bulletin of Counseling and Psychotherapy, 2025)
The mechanism of psychiatric disorders biologically has not been fully explained. The development of the pathogenesis of various diseases lately can be explained through the theory of inflammation. The theory of inflammation that may be related to the pathogenesis of psychiatric disorders is the kynurenine theory. From this kynurenine theory, the author tries to construct the mechanism of psychiatric disorders such as those that occur in cases of anxiety, depression, schizophrenia, insomnia to psychosomatic cases and epilepsy. From the various courses of psychiatric disorders, the author concludes that the mechanism of the occurrence of various psychiatric disorders is actually the same, but in the end, what distinguishes the occurrence of certain types of psychiatric disorders is the genetic factor of each individual who experiences it. It is essential to understand the mechanisms underlying psychiatric disorders from a biological perspective, as this knowledge serves as a foundation for managing such conditions, particularly through the use of psychopharmacological treatments and other adjunctive therapies.